Parental Genome Imbalance Causes Hybrid Seed Lethality as Well as Ovary Abscission in Interspecific and Interploidy Crosses in Nicotiana - He, Hai; Sadahisa, Kumi; Yokoi, Shuji; Tezuka, Takahiro (Frontiers in Plant Science, 2022)
Enhanced ovary abscission after pollination and hybrid seed lethality result in post-zygotic reproductive isolation in plant interspecific crosses. However, the connection between these barriers remains unclear. Here, we report that an imbalance in parental genomes or endosperm balance number (EBN) causes hybrid seed lethality as well as ovary abscission in both interspecific and intraspecific-interploidy crosses in the genus Nicotiana. Auxin treatment suppressed ovary abscission but not hybrid seed lethality in an interspecific cross between N. suaveolens and N. tabacum, suggesting that ovary abscission-related genes are located downstream of those involved in hybrid seed lethality. We performed interploidy crosses among N. suaveolens tetraploids, octoploids, and neopolyploids, and revealed hybrid seed lethality as well as ovary abscission in interploid crosses. Furthermore, a higher maternal EBN than paternal EBN caused these barriers, as previously observed in N. suaveolens × N. tabacum crosses. Altogether, these results suggest that maternal excess of EBN causes hybrid seed lethality, which in turn leads to ovary abscission through the same mechanism in both interspecific and interploidy crosses.